EFEK MEANINGFUL LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIKA SISWA SEKOLAH DASAR: PERAN MODEL PEMBELAJARAN NUMBER HEADS TOGETHER BERBANTUAN GEOBOARDS - Siti Rahmalia Natsir; Anisa Rizkayati; Eka Rosmitha Sari (Bajang Institute, 2025)
One of the 21st century skills is the ability to think critically. Critical thinking skills are essential for learning mathematics in elementary school. The purpose of this study is to determine the effect of meningful learning in the learning of Number Heads Together (NHT) assisted by geoboard media on the mathematical critical thinking ability of elementary school students. This study applies a quantitative research method with a One-Group Pretest-Posttest design. This design involved a sati experimental group, where there was no control group. There is a pretest before treatment and a posttest after treatment, so that the researcher can see the effect of treatment more accurately because it allows for a comparison of conditions before and after treatment. The geoboard-assisted NHT learning applied in this study is effective in improving the critical thinking skills of students in elementary schools. This increase is statistically proven through the non-parametric Wilcoxon Signed Ranks Test which is appropriate to be used when the data is not normally distributed, namely the value of Z = -2.889 with a significance level of 0.004 which is < 0.005 which shows a difference between conventional learning carried out by teachers and learning using the NHT model assisted by geoboards. The implementation of NHT assisted by geoboards encourages active discussion, conceptual understanding, and thorough student engagement, so it is highly recommended for mathematics learning in elementary schools in building students' critical thinking skills